Odpowiedzi

Najlepsza Odpowiedź!
2010-04-06T09:59:42+02:00
A² - b²..............(a-b)(a+b).......(a-b)(a+b)......a+b .......-3-1...... -4
_____________ = ---------------- =-------------- = ---------- =----------- =----=2/3
3a² - 6ab + 3b²....3(a2-2ab+b2) ....3(a-b)2 .......3(a-b)....3*(-3+1)... -6
2010-04-06T10:00:51+02:00
(a² - b²):(3a² - 6ab + 3b²)=[(a-b)(a+b)]:[3( a²-2ab+b²)]=[(a-b)(a+b)]:[3(a-b)²]=(a+b)/[3(a-b)]

a =-3
b =-1

a+b=(-3)+(-1)=-4
3*[(-3)-(-1)]=3*[(-3)+1]=3*(-2)=-6

(a+b)/[3(a-b)]=(-4)/(-6)=2/3

2010-04-06T10:02:35+02:00
A² - b²
_____________
3a² - 6ab + 3b² = (-3)²-(-1)²/3*(-3)²-6*(-3)*(-1)+3*(-1)²=

9-1/27-18+3=8/12=2/3

;))